Chiral quadridentate ligands based on amino acids: template syntheses and properties of the free ligands and their transition-metal complexes - Balla, József; Bernhardt, Paul V.; Buglyo, Peter; Comba, Peter; Hambley, Trevor W.; Schmidlin, Reto; Stebler, Sandra; Várnagy, Katalin (Dalton transactions, 1993)
The copper(II)-directed condensation of amino acids with formaldehyde and nitroethane has produced new open-chain quadridentate ligands stereoselectively and in generally high yield. The free ligands with pendant amine substituents may be isolated by zinc reduction of the copper(II) complexes. The reactions studied employed optically pure L-amino acids with non-co-ordinating side chains, racemic amino acids with non-co-ordinating side chains, amino acid mixtures and β-amino acids. The quadri- and quinquedentate ligands form very stable complexes with transition-metal ions, with their copper(II) complexes being generally stable down to pH ≈ 1. The isolation and spectroscopic properties (UV/VIS, IR, NMR and EPR) of cobalt(III) and copper(II) complexes of some of the amino acid-based ligands are reported. Condensation of racemic and mixed amino acids led to one out of three possible quadridentate ligands, and this stereoselectivity is interpreted based on a model involving the co-ordination of an organic nitro group. This mechanism is supported by qualitative molecular mechanics calculations. The crystal structures of the condensation products with β-alanine, ([Cu(mnp-β-ala)]·5H2O (mnp-β-ala = 6-methyl-6-nitro-4,8-diazaundecanedioate), and the Zn-HCl reduction product of the condensation with glycine [Cu(Hampgly)Cl]·2H2O (ampgly = 5-amino-5-methyl-3,7-diazanonanedioate), have been determined. In the former structure the CuII is in a distorted trigonal-bipyramidal environment with the fifth site being a co-ordinated carboxylate oxygen from an adjacent molecule, while in the latter CuII has a square-pyramidal co-ordination with an apical chloride ligand.
Gesehen am 05.09.2022